Developments in Pediatric Ventricular Assist Device Support. Issue 6 (November 2019) - Tume, Sebastian C.; Conway, Jennifer; Ryan, Kathleen R.; Philip, Joseph; Fortkiewicz, Justine M.; Murray, Jenna
Mechanical support devices have revolutionized the management of circulatory failure. This has been met by a dramatic increase in ventricular assist device (VAD) utilization in children over the last two decades. Previous wide gaps in experience and knowledge have significantly narrowed in the recent years. As we continue to gain experience with this technology, we face new challenges such as complex congenital circulations and small patient size. The emergence of new pharmacologic therapies and device technology offers more opportunities and requires constant adjustment in practice. As we continue to embark on this journey, constant insight is needed to refine patient selection criteria, minimize complications, and continue to push the field for safer smaller devices to accommodate these complex patient populations. In this review focused at inpatient critical care environment, we discuss the recent field developments and focus on challenging patient populations, the emergence of temporary support, management of anticoagulation, and diagnostic approach to stroke in the setting of VAD support.